The Role of Immersive Virtual Realities: Enhancing Science Learning in Higher Education - Talia Tene; Marco Guevara; Gabriel Moreano; John Vera; Cristian Vacacela Gomez (Emerging Science Journal)
Objective: This systematic review aims to map out the role of immersive technologies, specifically virtual and augmented realities (VR and AR), in enhancing learning outcomes within higher education science programs, providing a clearer understanding of their pedagogical value. Methods: Leveraging extensive database searches in Scopus and Web of Science, an initial phase of 172 articles was identified. Through a meticulous process of screening based on inclusion and exclusion criteria, this was refined to 33 important articles. These articles were further analyzed to identify distinct structural elements regarding VR and AR interventions and their effects on educational outcomes. Analysis: Each study was evaluated for its contribution to pedagogical methods, with a focus on quantifiable changes in student performance and engagement. Results: The analysis revealed that immersive technologies are being applied across various stages of the academic crossing, from introductory courses to advanced laboratory work. Particularly, 18 articles demonstrated a significant positive or increased impact on learning outcomes. Conclusions: The review confirms that VR and AR possess a transformative potential for higher education, particularly in the sciences. These technologies not only captivate students' interest but also facilitate deeper understanding and retention of complex material. The evidence suggests that VR and AR can substantially enhance the educational experience when implemented thoughtfully. Future research should aim to expand upon these findings, exploring the longitudinal impact of immersive technologies on learning and their potential to democratize education.